Preliminary results at IITA in breeding plantain for black sigatoka resistance in Africa - Swennen, Rony L.; Vuylsteke, D.R. (1991)
Africa accounts for 50 of all plantain produced in the world. These plantains are overwhelmingly import as a food crop for local consumption. Black sigatoka has now invaded Africa, thereby endangering this important food source. The long term solution lies in the creation of black sigatoka resistant plantains. The available Musa germplasm at IITA was screened for female fertility with AA black sigatoka resistant diploids. Sixteen `French' plantains and seven `False Horn' plantains produced seed. Hybrid progeny was rescued using embryo culture techniques and the first black sigatoka resistant tetraploid plantain hybrid are currently under evaluation in the field.